Structural complexity and physical mechanism of self-assembled lipid as nanocarriers: A review - Ilias, Nazhan; Richmond, Rocky Vester; Selvarajah, Gayathri Thevi; Mat Azmi, Intan Diana; Ajat, Mokrish (Malaysian Society of Molecular Biology and Biotechnology, 2023)
Lipids such as glyceryl monooleate, phosphatidylcholine, and monoglyceride (CITREM) possess an amphipathic property that allows them to self-assemble into a complex internal structure when interacting with an aqueous solution. Since amphiphilic molecules possess hydrophilic heads and lipophilic tails, hydrophobic effects cause the spontaneous activity of the molecular rearrangement. The self-organization of the molecules often results in the phases of lipid polymorphism, for example microemulsion, inverse bicontinuous cubic (Q2), discontinuous hexagonal (H2), and micellar cubic (I2) Fd3m. Interestingly, these lamellar and non-lamellar phases have been applied in the development of nanocarriers for drug delivery due to their ability to provide a sustained drug release system, better drug bioavailability, and improved overall treatment. However, the attention that they are receiving from their application is not comparable to our understanding of the mechanisms involved in their synthesis. Elucidation of the spontaneous process helps in predicting and tuning the internal structure of an amphiphilic molecule to suit its application. Therefore, this review discusses the formation of lipid polymorphism from the thermodynamic point of view, critical packing parameter, and modified stalk theory.